THE EUROPEAN UNION'S CONTRIBUTION TO COUNTERING THE EFFECTS OF THE ALMOST TWO-YEAR RUSSIA'S WAR OF AGGRESSION AGAINST UKRAINE - Vataman, Dan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
For almost two years, Ukraine has faced the Russia's full-scale invasion and war of aggression, an illegal, premeditated and illegitimate act that represents an attack not only against the sovereignty and territorial integrity of Ukraine, but also a flagrant violation of international law, including the Charter of the United Nations. The brutal military aggression against Ukraine caused destruction, material damages and widespread suffering for civilians, which has led to the worst humanitarian crisis in Europe since the end of the Second World War. Consequently, the dramatic situation in Ukraine has caused new and unanticipated challenges for neighbouring countries, including Romania, given their proximity to the conflict zone. Therefore, the purpose of this study is to highlight, first of all, the EU emergency response to Russia's invasion of Ukraine and also solidarity with Ukraine. Taking into account Romania's status as an EU member, the next objective of this study is to point out Romania's involvement and comprehensive support for Ukraine in the humanitarian field, especially on protection and inclusion of Ukrainian refugees. For almost two years, Ukraine has been facing the Russia's full-scale invasion and war of aggression, an illegal, premeditated and illegitimate act that represents an attack not only against the sovereignty and territorial integrity of Ukraine, but also a flagrant violation of international law, including the Charter of the United Nations. The brutal military aggression against Ukraine caused destruction, material damages and widespread suffering for civilians, which has led to the worst humanitarian crisis in Europe since the end of the Second World War. Consequently, the dramatic situation in Ukraine has caused new and unanticipated challenges for neighbouring countries, including Romania, given their proximity to the conflict zone. Therefore, the research undertaken for this study has been focused, first of all, on the EU's contribution to countering the effects of the Russia’s war of aggression against Ukraine, with accent on the EU emergency response to Russia's invasion of Ukraine and also solidarity with Ukraine. Taking into account Romania's status as an EU member, the next objective of this study is to point out Romania's involvement and comprehensive support for Ukraine in the humanitarian field, especially on protection and inclusion of Ukrainian refugees. In order to achieve these proposed objectives, qualitative and quantitative research methods were utilised, written data being used, but also logical or statistical observations to draw conclusions. As well, inductive reasoning conducted the research from the specific to the general situations, while deductive reasoning allowed to make an inference by going from general premises to specific conclusions.